Designing public space for an ageing population : improving pedestrian mobility for older people - Musselwhite, Charles B. A. (Emerald Publishing Limited, 2021)
Designing Public Space for an Ageing Population examines the barriers older people face by being a pedestrian in the built environment and demonstrates how to overcome them. Drawing on research carried out across the globe, and framed around Bourdieu's theory of capitals, this book establishes how to overcome restrictions and barriers to mobility including: - Infrastructure capital, such as technology, services, roads, pavements, finance and economics - Social capital, for example friends, family, neighbourhood and community - Cultural capital (norms, expectations, rules, laws) - Individual capital (skills, abilities, resilience, adaptation and desire and willingness to change) The book demonstrates that the public realm must be safe and accessible, but also attractive and desirable to an ageing population. The book includes case studies presenting solutions around CABE's objectives of urban design, notably: safe and accessible space including ease of movement; legible space, including adaptability, diversity and choice and; distinctive and aesthetically pleasing space, including character, continuity and quality.
Keywords: Public spaces -- Social aspects.; Barrier-free design for older people.; Pedestrian areas -- Planning.; Architecture -- Human factors.; Public spaces -- Barrier-free design.; Social Science -- Demography.; Population & demography.; elektronické knihy; electronic books